OBSERVAÇÕES SÔBRE A IRRITABILIDADE DO ESTIGMA DE Pyrostegia venusta MIERS. - Arens, Karl; Cesar, Oswaldo (REVISTA DE AGRICULTURA, 2016)
OBSERVAÇÕES SÔBRE A IRRITABILIDADE DO ESTIGMA DE Pyrostegia venusta MIERS.